2020
DOI: 10.1111/imj.14396
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcal bacteraemia ‘silent but deadly’: a population‐based cohort study

Abstract: Background: The high mortality rate of patients with enterococcal infections has been shown to be associated with the severity of underlying comorbidities.Aims: To characterise the epidemiology, clinical characteristics, outcomes and predictors of mortality in patients with enterococcal bacteraemia. Methods:This was a retrospective cohort study of all enterococcal bacteraemia episodes in the Barwon region between January 2010 and March 2017. We assessed the epidemiology, clinical characteristics, outcomes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 23 publications
4
12
0
4
Order By: Relevance
“…Moreover, we detected that urinary cancer was associated with bacteremia in patients with UTIs. In a recent study, urological cancer was also associated with bacteremia (20). These results support that regardless of E. faecalis-and E. faeciumcolonizing urinary tract infections, it is difficult for these pathogens to cross the urinary epithelium when innate immunity is preserved, but when it exists, rupture of the epithelial barrier can result in bacteremia.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Moreover, we detected that urinary cancer was associated with bacteremia in patients with UTIs. In a recent study, urological cancer was also associated with bacteremia (20). These results support that regardless of E. faecalis-and E. faeciumcolonizing urinary tract infections, it is difficult for these pathogens to cross the urinary epithelium when innate immunity is preserved, but when it exists, rupture of the epithelial barrier can result in bacteremia.…”
Section: Discussionsupporting
confidence: 56%
“…Our results are consistent with other findings, and we showed that neutropenia, solid organ transplant, bone medullary transplant, and immunosuppression were also risk factors for bacteremia in patients with tract urinary infection caused by Enterococcus spp. (16,20). These are the same classic risk factors in patients with bacteremia, regardless of other origins (4).…”
Section: Discussionmentioning
confidence: 99%
“…Among the different comorbidities demonstrated by the patients, the most important were urinary disorders or severe systemic diseases. Among urological diseases, urological cancer has been described as a risk factor for Enterococcus UTIs (19,20). It is possible, as is the case in bacteremia associated with colorectal cancer (20), that lesions due to urinary epithelial colonization can be one of the most important predictive risk for urinary infections caused by Enterococcus.…”
Section: Discussionmentioning
confidence: 99%
“…Enterococcus species are generally considered to be of low virulence, so the previously reported association of enterococcal infections with higher mortality and a poor prognosis could be due to the association of these infections with malignancy and [“other”?] chronic comorbid conditions [ 16 , 17 ]. In our current study, harboring an isolate displaying vancomycin resistance was associated with higher infection-related and all-cause mortality, attributed by multivariate analysis to isolation of E. faecium and hospitalization in a critical-care setting.…”
Section: Discussionmentioning
confidence: 99%